The impact of COVID-19 infection on musculoskeletal pain and its associating factors: a cross-sectional study - Li, Hongyan; Zhuang, Shiyang; Lin, Yiming; Huang, Mei; Zhang, Wenming; Zhang, Xuehui; Lin, Yunzhi; Zhang, Chaofan (Frontiers in Public Health, 2024)
Objectives: Musculoskeletal pain after COVID-19 infection remains a concerning long-term complication of COVID-19. Here, our study aimed to investigate the prevalence of musculoskeletal pain associated with COVID-19 (MSPC) and healthcare-seeking behaviors, as well as the associating factors. Methods: A cross-sectional survey was conducted using convenience sampling and distributed to participants anonymously through the online platform Credamo. Demographic and characteristic data of the participants were collected and analyzed. Logistic regression analysis was employed to investigate potential factors associated with MSPC and healthcare-seeking tendencies. Results: A total of 1,510 participants responded to the survey, with 42.6% (643 individuals) exhibiting MSPC. Higher education level and a greater number of concomitant symptoms were significant risk factors for MSPC, while longer exercise duration and higher PSS-10 scores were protective factors. Additionally, higher income level, frequency and severity of pain, and greater PSS-10 scores increased healthcare-seeking intention. Conclusion: A significant proportion of individuals experience MSPC. Education level and concomitant symptoms were risk factors for MSPC, while exercise duration and PSS-10 score were potential protective factors. Income level, frequency and severity of pain, and PSS-10 score are significantly related to the willingness to seek medical treatment for MSPC.